BASIC CONSTRUCTION PRINCIPLES FOR MULTI-FUNCTIONAL HYDRO AGROLANDSCAPE SYSTEMS - Mustafayev Zhumakhan Suleimenovich,; Sagaev Abzhappar Abiltayevich,; Alimbaev Erzhan Nurlanovich,; Pchelkin Victor Vladimirovich, (Academic Journal of Physical and Chemical Sciences, 2020)
Based on the principles of natural analogies, the necessary diversity, the ability of soil formation and the integration of knowledge, multifunctional hydroagrolandscape systems have been developed, including multifunctional systems (crop rotation fields and irrigation technique), which ensure the fulfillment of the ecological and economic functions of the soils of hydroagrolandscape systems. Multifunctional hydro-agrolandscape systems for the purposeful regulation of the soil-forming process on irrigated crop rotation fields by designing crop rotation and an irrigation system on irrigated lands (hydro-agricultural landscape system) with the linkage of agricultural crops to irrigation equipment and technology, which move along with agricultural crops according to the rotational scheme, adopted in the crop rotation, ensure the maximum possible use of solar energy for the soil-forming process in specific natural and climatic conditions. The environment-forming functions of a multifunctional hydroagrolandscape system are provided on the basis of the use of integral criteria to ensure the agroecological sustainability of irrigated crop rotations (hydroagrolandscapes), taking into account geoecological restrictions, that is, the weighted average irrigation rate (water demand deficit) of agricultural crops in the crop rotation should not exceed the deficit of the ecological water requirement of agricultural land systems. Thus, the design of highly productive hydrolandscape systems requires ensuring compliance with not only the principles of the necessary diversity and natural analogies, based on the creation of se-rotations with mobile irrigation techniques to control and regulate soil-forming processes, that is, the soil as an object of influence (reclamation) performing an ecological function , and agricultural crops as a subject perform an economic function, requires the need, on the basis of the principle of knowledge integration, to form ways of regulating the natural process that provide targeted regulation and control of soil-forming processes as environment-forming systems.